Ageing, health and life satisfaction of the oldest old: an analysis for Germany - Wencke Gwozdz; Alfonso Sousa-Poza (Institute for the Study of Labor (IZA), 2009)
This analysis uses data from the German Socio-Economic Panel (GSOEP) and the Survey on Health, Ageing and Retirement in Europe (SHARE) to assess the effect of ageing and health on the life satisfaction of the oldest old (defined as 75 and older). We observe a U-shaped relationship between age and levels of life satisfaction for individuals aged between 16 and approximately 65. Thereafter, life satisfaction declines rapidly and the lowest absolute levels of life satisfaction are recorded for the oldest old. This decline is primarily attributable to low levels of perceived health. Once cohort effects are also controlled for, life satisfaction remains relatively constant across the lifespan.
urn:nbn:de:101:1-20090327209
Keywords: I18; I19; J28; 330; Life satisfaction; health; oldest old; Alte Menschen; Lebenszufriedenheit; Gesundheit; Deutschland